Dyadic interview guide piloted in Tanzania to assess the contributions of each spouse to the household's decision-making process - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The first draft of the guide was completed in September 2020. A workshop was held in Stone Town, Zanzibar in October 2020 with the partners of a climate-smart agriculture project to refine the tool before pre-testing it with two couples and then piloting it with 30 couples.